Liberty in the Things of God: The Christian Origins of Religious Freedom - Wilken, Robert Louis (Yale University Press, 2019)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Acknowledgments -- Introduction -- Chapter 1 Endowed with Freedom -- Chapter 2 A Christian Society -- Chapter 3 The Two Swords: Reformation in Germany -- Chapter 4 Custodians of Both Tables: Switzerland -- Chapter 5 Two Religions in One City: France -- Chapter 6 Freedom of Worship: The Netherlands -- Chapter 7 Sturdy Piety: Catholics in England -- Chapter 8 Seeking Faith's Pure Shrine: English Separatists -- Chapter 9 Liberty Necessary unto Human Nature -- Conclusion -- Epilogue -- Appendix: Thomas Jefferson and Tertullian -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Z -- Index of Biblical Citations.